The Hoogsteder Journal. (Den Haag : Hoogsteder & Hoogsteder, 1996)
From 1996 to 2005 Hoogsteder & Hoogsteder published The Hoogsteder Journal in Dutch and English. The Journals contain articles about Old Master paintings written by various authors, such as Edwin Buijsen, Marieke Spliethoff and Willem Jan Hoogsteder. The aim of the articles is to provide insight to collectors, art historians and art lovers. (hoogsteder.com)
Vroeger : the Hoogsteder-Naumann Mercury
Nederlands
Tijdschriften